MENUMBUHKAN KREATIVITAS MEMBUAT GERAK TARI DENGAN MODEL PEMBELAJARAN LINGKUNGAN DI PEMBELAJARAN OLAH TUBUH BAGI SISWA SMK - Amanda, Tia (Program Studi Pendidikan Tari FBS UNJ, 2020)
This paper describes the results of research to improve students' creativity in making dance movements through the application of an environmental learning model, for class X students in physical exercise learning at SMK Negeri 57 Jakarta. The goal is to increase data on student creativity improvement. This research was conducted using the Classroom Action Research method and took place from September to December 2019, with a cycle of planning, observation, and reflection. Data obtained by observation, interview and questionnaire techniques. The results of this study indicate that creativity in students' dance is 70.83 (63.88%) from the average in the first cycle, and 88.5 (91.66%) from the average in the second cycle.